Researching cultural differences in health - Kelleher, David, 1935-; Hillier, S. M. (Sheila M.), 1944- (Routledge, 1996)
Offers a range of accounts of how people in ethnic minority groups perceive and manage their illnesses. Illnesses discussed include: sickle-cell disorder, mental illness, hypertension, and coronary heart disease.